Research design for studying development in border areas: case studies towards the big picture? - Sarolta Németh; Ágnes Németh; Virpi Kaisto (Belgeo)
This paper is concerned with the research design of four recent border related research projects, all operating in European multi-case study frameworks. All these studied projects have the aim of producing, on the one hand, regionally specific research results and, on the other hand, results that bear relevance to general border theories. Furthermore, most of these researches have to provide messages for policy makers and not only on the local-regional but on a more general, European level. This paper discusses what research designs the projects have chosen to operate in to reach all of these objectives. The focus is on two major aspects that have an impact on the research designs and are connected to the need for abstraction from specific contextual cases: comparative framework and policy relevance on different levels.